The impact of immigration on Portuguese intra-industry trade - Nuno Carlos Leit\~ao (Fondazione Eni Enrico Mattei (FEEM), 2013)
This paper investigates the relationship between intra-industry trade (IIT) and immigration flows using a gravity model for the period 2000-2010 between Portugal and European Union's Member States (EU-27). The present study uses the methodology of Kandogan (2003) for separating IIT into its components horizontal (HIIT) and vertical intra-industry trade (VIIT). Using a panel data approach, our study find that immigration has a positive influence on Portuguese intra-industry trade. These results indicate that the immigration can reduce transaction costs between home and host country. We also consider in econometric model, the economic dimension which appears to exercise a positive effect on IIT. Our results confirm the hypothesis that there is a negative effect of transportation costs on trade.
Keywords: C20; C30; F12; L10; 330; gravity model; horizontal and vertical intra-industry trade immigration and panel data